Revised Evaluation of Hemodilution Response in the Semi-Closed Loop Infusion System - Markevicius, Vytautas; Cincikas, Darius; Porvaneckas, Narunas; Stankevicius, Edgaras; Navikas, Dangirutis; Andriukaitis, Darius; Sipylaite, Jurate; Svediene, Saule; Uvarovas, Valentinas; Satkauskas, Igoris; Kvederas, Giedrius; Valinevicius, Algimantas; et al. (Elektronika ir Elektrotechnika, 2016)
A mini volume loading test (mVLT) method is used for decision making in our prototype semi-closed loop infusion system (SCLIS). The mVLT fluid protocol consists of hemodilution response-guided mini fluid challenges. Each mini fluid challenge (MFC) consists of a 2.5 ml kg-1–5 ml kg-1 crystalloid bolus infused over 2 min–5 min and followed by a 5 min period with no fluids. Arterial plasma dilution efficacy (aPDE) of a MFC is calculated from invasively measured hemoglobin (aHb) before and after each MFC. Capillary plasma dilution efficacy (cPDE) is calculated from non-invasively measured hemoglobin (SpHb). The zero or negative arterio-capillary plasmadilution efficacy difference (acPED ≤ 0 p.d.u.) is an indication of hemodilution non-response and imminent edema. However, it requires both invasive and non-invasive hemoglobin measurements. A non-invasive assessment of hemodilution response within the mVLT method would increase its practical application and reduce costs further enhancing its applicability in the SCLIS. This possibility exists if the cPDE could reliably predict the acPED value or the hemodilution response (the presence of acPED within a range of > 0) or non-response (acPED ≤ 0). We report a retrospective observational study in an elective total knee arthoplasty (TKA) setting. The 2.5 ml kg-1 boluses were used in six MFCs in both pre- and post-operative mVLT sessions. The primary objective was to assess the accuracy of cPDE in predicting the hemodilution response using the receiver operating characteristic (ROC) curve and gray zone approaches. Our secondary objective was to investigate the feasibility of a statistical optimization method (SOM) in predicting the acPED. The analysis included 480 paired values of cPDE and acPED. The best cut-off value for cPDE was 0.015 p.d.u. (specificity = 0.84, sensitivity = 0.90). The gray zone identified a range of cPDE values between 0.013 and 0.028 (p.d.u.) for which the hemodilution response could not be indicated reliably. The 14 % of the cPDE values were in this range. The non-invasive evaluation of hemodilution response is acceptably accurate in the perioperative TKA setting. The mVLT algorithm within our prototype SCLIS was upgraded by implementing the results of the present study. DOI: http://dx.doi.org/10.5755/j01.eee.22.1.12826